Production of polygalacturonases by aspergillus section Nigri strains in a fixed bed reactor - Maciel, Marília de Holanda Cavalcanti (2013)
Polygalacturonases (PG) are pectinolytic enzymes that have technological, functional and biological applications in food processing, fruit ripening and plant-fungus interactions, respectively. In the present, study a microtitre plate methodology was used for rapid screening of 61 isolates of fungi from Aspergillus section Nigri to assess production of endo- and exo-PG. Studies of scale-up were carried out in a fixed bed reactor operated under different parameters using the best producer strain immobilised in orange peels. Four experiments were conducted under the following conditions: the immobilised cells without aeration; immobilised cells with aeration; immobilised cells with aeration and added pectin; and free cells with aeration. The fermentation was performed for 168 h with removal of sample every 24 h. Aspergillus niger strain URM 5162 showed the highest PG production. The results obtained indicated that the maximum endo- and exo-PG activities (1.18 U·mL-1 and 4.11 U·mL-1, respectively) were obtained when the reactor was operating without aeration. The microtitre plate method is a simple way to screen fungal isolates for PG activity detection. The fixed bed reactor with orange peel support and using A. niger URM 5162 is a promising process for PG production at the industrial level.